2008
DOI: 10.1134/s000629790803019x
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeleton inhibitors combined with TRAIL induce apoptosis in HeLa carcinoma cells overexpressing antiapoptotic protein Bcl-2

Abstract: TRAIL (Apo2L), a cytokine from the family of tumor necrosis factors (TNF), causes apoptosis in various types of tumor cells but is not toxic for normal cells. Recombinant TRAIL obtained using an original method stimulates the release of cytochrome c from mitochondria into the cytoplasm and apoptosis in HeLa carcinoma cells. Expression of oncoprotein Bcl-2 in these cells blocks both processes. The microtubule inhibitors taxol, nocodazole, and colcemid, as well as an inhibitor of actin microfilaments cytochalasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…4). We have shown earlier that the inhibitor of microtubules, taxol and the inhibitor of actin microfilaments, cytochalasin D enhanced efficiency of TRAIL and allow it to overcome antiapoptotic effect of Bcl-2 [20]. All the DR5-selective TRAIL variants did not lose the capacity to break Bcl-2 block in combination with the inhibitors of cytoskeleton (Fig.…”
Section: Generation Of New Dr5-selective Trail Mutant Variantsmentioning
confidence: 72%
See 1 more Smart Citation
“…4). We have shown earlier that the inhibitor of microtubules, taxol and the inhibitor of actin microfilaments, cytochalasin D enhanced efficiency of TRAIL and allow it to overcome antiapoptotic effect of Bcl-2 [20]. All the DR5-selective TRAIL variants did not lose the capacity to break Bcl-2 block in combination with the inhibitors of cytoskeleton (Fig.…”
Section: Generation Of New Dr5-selective Trail Mutant Variantsmentioning
confidence: 72%
“…In our previous studies we have demonstrated that expression of Bcl-2 blocks TRAIL-induced release of cytochrome c from mitochondria into cytosol and apoptosis in Hela cells [20]. No one of the DR5-selective TRAIL variants could overcome this block of apoptosis (Fig.…”
Section: Generation Of New Dr5-selective Trail Mutant Variantsmentioning
confidence: 93%
“…While only few compounds contributed to tubulin enrichment (Table ), the HTS actives included antimitotic agent grisofulvin and several colchicine derivatives, suggesting that this correlation is authentic. Indeed, microtubule-targeted agents nocodazole and paclitaxel are reported to sensitize cancer cells to TRAIL. ,, The enrichment analysis also identified ABL, Src, FAK, PAK1, and CDK5, kinase targets linked to cytoskeleton arrangements and tubulin stability (Figure ), but these targets proved less fruitful. The Src, ABL, and CDK5 inhibitors primarily inhibited GSK3, and GSK3 could not be discounted adequately.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, microtubule-targeted agents nocodazole and paclitaxel are reported to sensitize cancer cells to TRAIL. 55,67,56 The enrichment analysis also identified ABL, Src, FAK, PAK1, and CDK5, kinase targets linked to cytoskeleton arrangements and tubulin stability (Figure 3), but these targets proved less fruitful. The Src, ABL, and CDK5 inhibitors primarily inhibited GSK3, and GSK3 could not be discounted adequately.…”
Section: ■ Resultsmentioning
confidence: 99%